2019
DOI: 10.22373/ej.v7i1.4508
|View full text |Cite
|
Sign up to set email alerts
|

VISUALIZATION AND COMPREHENSION: Corroborating children’s reading ability

Abstract: This study aimed at finding out the influence of visualization on students’ reading comprehension ability. Quantitative approach was employed in carrying out this research. The data were collected through test as it was the main instrument of this study. The data analysis was carried out using manual statistics calculation to find out the mean score before and after the treatment. From the result, it was obtained that the most effect that visualization has is on the inferring; second, it is on details; then it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Evidence shows that reading skills play a significant role in terms of promoting visualisation (Moriyanti et al, 2019). In line with this, Mulligan (2011) emphasises the need for teaching methods that optimise reading skills in order to enhance the visualisation of word problems.…”
Section: Improving Reading Skillsmentioning
confidence: 86%
“…Evidence shows that reading skills play a significant role in terms of promoting visualisation (Moriyanti et al, 2019). In line with this, Mulligan (2011) emphasises the need for teaching methods that optimise reading skills in order to enhance the visualisation of word problems.…”
Section: Improving Reading Skillsmentioning
confidence: 86%
“…Sabiq (2018) also found that visual content improved students' motivation and reading achievement. It terms of its effectiveness in enhancing reading comprehension, Moriyanti et al, (2019) found that visualization affect students reading comprehension in terms of inferring, details, and main idea. The use of visualization also more effective than non-visualized material because it provides motion that helps the students enhance their understanding (Roohani et al, 2015) Even though it is in the context of online learning, teachers still have to prepare learning materials that are attractive to students (Rasmitadila et al, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Sabiq (2018) also found that visual content improved students' motivation and reading achievement. It terms of its effectiveness in enhancing reading comprehension, Moriyanti et al, (2019) found that visualization affect students reading comprehension in terms of inferring, details, and main idea. The use of visualization also more effective than non-visualized material because it provides motion that helps the students enhance their understanding (Roohani et al, 2015) Even though it is in the context of online learning, teachers still have to prepare learning materials that are attractive to students (Rasmitadila et al, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%